(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The paper makes an effort to study the role of four theoretical approaches to business ethics under consideration namely Utilitarianism, Managerial egoism, Deontological Ethics and Virtue Ethics on three prominent ethnic groups namely Bodo, Mishing and Rabha. The study was exploratory cum descriptive in nature and conducted on a sample of 1200 respondents comprising of 400 respondents from each community. Stratified cum convenience sampling technique was used with a structured questionnaire schedule for field study in the state of Assam. The field study found that the people of the Bodo community are highly influenced by Managerial Egoism and Deontological Ethics whereas the people of the Mishing community are highly influenced by Utilitarianism and Virtue Ethics. Lastly the people of the Rabha community are influenced by a mixture of Managerial Egoism, Deontological Ethics and Virtue Ethics. These are vital input for managers in taking important decisions in the field of management.